Measures of Spatial and Demographic Disparities in Access to Urban Green Space in Harbin, China - Qian Xie; Ming Lu (Complexity)
Access to urban green space (UGS) is associated with the enhancement of health and disparities in access generate issues of spatial equity and socioenvironmental justice. The aim of this study is to measure spatial accessibility and investigate access disparities to UGSs in urban areas of Harbin, China. A Gaussian-based two-step floating catchment area method and spatial autocorrelation analysis were used to measure the accessibility and evaluate its distribution patterns in residential tracts. Bivariate correlation was employed to examine the statistical relations between demographic characteristics of residential tracts and green space access. The results show that most residential tracts have minimal green space access within walking distance, while a few have limited access within cycling distance. Additionally, spatial disparities were found with low-accessibility tracts clustering in the center of the city, while high-accessibility tracts were located in northern and southern suburbs. Demographic disparities were also identified in the study: females have less access to UGS than males, areas with a high birth rate generally have more access, and population density is negatively associated with UGS access. The findings not only indicate that Harbin has an uneven distribution and disproportionate provision of UGS for urban residents but also identify which areas and population groups within the city are disadvantaged in access to UGS and thus provide suggestions for future construction and provision of UGS.